15. VOC analysis: A new tool to study olfactory impairment. Issue 1 (January 2015) - Sartucci, F.; Barloscio, D.; Giorli, E.; Bocci, T.; Torzini, A.; Mazzatenta, A.
<x xml:space="preserve">Abstract</x> Head trauma is a common cause of smell impairment; depending on its severity anosmia might occur in most of cases. Traumatic olfactory impairment is consequent to the severity of the mechanical distress that principally affect the peripheral olfactory area such as olfactory sensory neuron (OSN) axon; mainly olfactory bulb, olfactory tract and rarely the central areas of olfactory projection. A subject with a traumatic anosmia was followed over a year, from the trauma, by using new psychophysical tests (threshold, discrimination, identification), developed for Italian population, EEG and Volatile Organic Compounds analysis. The olfactory threshold, discrimination and identification are respectively 6.33 ± .33se dilution step, 47% and 27% at the time of the trauma; two months later were improved at 5 ± 1 se, 53% and 52.5%; lastly, one year later, were 4.33 ± .33 se, which is normal for age matched category, 100% and 93%. The EEG and VOC recordings similarly showed the recovery of response to odorants. A short term olfactory impairment is represented by the time required to the OSN regeneration. Because of a growing interest in the investigation of smell disorders in research and clinical practice a tool for the assessment of the olfactory function is essential.